Determinants of housing purchasing decision among buyers in Klang Valley / Muhammad Idzuddin Ahmad Nazir and Hazirah Md. Nor - Ahmad Nazir, Muhammad Idzuddin; Md. Nor, Hazirah (Faculty of Business and Management, 2014)
This research is conduct to carry out the “Determinants Of Housing Purchasing Decision Among Buyers In Klang Valley”. In order to investigate the differ findings from other previous researcher, we have decided the relationship between house price, location, features, affordability of house buyers and house purchase decision. The objectives of this research are to analyze the relationship between prices of house, location, features of the house and affordability of house buyers with house purchase decision as well as to determine the most significant determinants that influencing the purchase decision among of house buyers in Klang Valley. Besides questionnaire as primary data, all the data were obtained from the secondary data. Journals and related information were obtained from Internet and journals. The variables will be analyzed by using the frequency distribution, the reliability analysis, descriptive statistical analysis, correlation analysis and multiple regression analysis. As results, we found that house price, house location, house features and affordability of house buyers have significant relationship with house purchase decision whereas house price is most influenced the housing purchase decision. The future researcher should survey more about this topic and make sure that all the information regarding house purchase decision can be used and can help the house buyer to make a good decision.